Methyl phosphotriesters in alkylated DNA are repaired by the Ada regulatory protein of E. coli. - McCarthy, T V (1985)
The E. coli ada+ gene product that controls the adaptive response to alkylating agents has been purified to apparent homogeneity using an overproducing expression vector system. This 39 kDa protein repairs 0(6)-methylguanine and 0(4)-methylthymine residues in alkylated DNA by transfer of the methyl group from the base to a cysteine residue in the protein itself. The Ada protein also corrects one of the stereoisomers of methyl phosphotriesters in DNA by the same mechanism, while the other isomer is left unrepaired. Different cysteine residues in the Ada protein are used as acceptors in the repair of methyl groups derived from phosphotriesters and base residues.